Physical Models of Plasma Microfield. (14th September 2009) - Demura, A. V.
Abstract : The present review is devoted to the current status of microfield notion that was so successful and profitable for experimental and theoretical studies of plasma in gas discharges and thermonuclear modeling installations for many decades. The physical aspects and ideas of the main generally used microfield models are described and analyzed in detail. The review highlights the remaining vague and unclear questions in the subject.